VALIDITAS DAN RELIABILITAS INSTRUMEN PENILAIAN MEMBACA SHORT FUNCTIONAL TEXT PADA SISWA SMP KELAS VIII - Zulpan Zulpan; Ahmad Rusli (Jurnal Pendidikan Guru, 2020)
The objective of this study is description validity and reliability on instrument assessment of reading short functional text eight grade junior school. This research method is quantitative description, it have described validity and reliability of instrument. The research subjects were in 100 students of eight grade junior school. Data collection in this study is validation sheet to expert judgment and result of the field for students. This research data analyze is content validity by expert judgment using Aiken's V formula and reliability instrument by using Two Way Anova helping SPSS software than the results computing by Ebel formula. Research finding are: the validity of instrument 0.8 is said valid, the reliability instrument 0.731 is said reliable the reliability coefficient of instrument 0.920 can be interpreted that instrument assessment of short functional text has consistency. The instrument assessment of reading short functional text can be concluded valid and reliable.